Exploring family physicians’ mental health referrals via centralized referral systems in Quebec, Canada: a qualitative descriptive study - Jessica Spagnolo; Marie Beauséjour; Marie-Josée Fleury; Jean-François Clément; Claire Gamache; Lyne Couture; Carine Sauvé; Shane Knight; Christine Gilbert; Richard Fleet; Helen-Maria Vasiliadis (SSM - Mental Health)
Background: Centralized referral mechanisms anchored in primary care have been implemented to facilitate timely and appropriate access to health care in Quebec, Canada, like via Centre de répartition des demandes de services (CRDS), a regionally centralized referral system used by family physicians (FPs) for new requests to specialty care, including psychiatric services. CRDS for psychiatry was implemented in 2019, where local centralized referral systems to psychosocial or psychiatric services (Guichets d'accès en santé mentale adulte (GASMA)) were already operating. We aimed to: 1) explore FPs' use of CRDS for psychiatry; 2) better understand the functioning and potential complementarity of CRDS and GASMA, including by visually mapping these pathways; and 3) identify factors that may influence their use and functioning. Methods: A qualitative descriptive study with 20 participants working in the healthcare sector was conducted. Thematic analysis was employed. Results: Mental health referral pathways were mapped, with FPs as focal points. Factors identified as influencing referral mechanisms' use and functioning included: 1) challenges related to the communication of ministerial directives on the use/functioning of centralized referral systems; 2) stakeholders' perceptions on the regionally centralized system's objectives for service access; 3) collaborations between clinicians and the regionally centralized system; 4) perceived added value of the regionally centralized system compared to pre-existing centralized local referral systems; and 5) key organizational/system-level mental health challenges and facilitators. Recommendations to improve these pathways' use, functioning, and complementarity included clarifying directives and roles within trajectories, and improving communication between the regionally centralized and local systems already in place, as well as addressing organizational/system-level challenges to mental health care. Conclusions: Findings inform on improvements for mental health service access, delivery, and continuity via centralized referral systems anchored in primary care and used by FPs; and access challenges via pathways and solutions to optimize mental health service trajectories.